Supply Chain Management - Sharon Williams (Cambridge University Press, 2025)
Creating a well-integrated, resilient, and highly transparent supply chain is central to effective and safe patient care. But managing healthcare supply chains is complex; common challenges include the underuse, overuse, and misuse of health resources. This Element introduces the key principles and definitions of healthcare supply chains. Practical insights into the design and operation of healthcare supply chains are provided. Core characteristics of effective supply chain management such as performance management, systems thinking, and supply chain integration are examined along with the application of specific supply chain design and improvement approaches. Finally, the Element proposes areas that require further development both in research and practice. This title is also available as open access on Cambridge Core.